2019
DOI: 10.1074/mcp.ra119.001356
|View full text |Cite
|
Sign up to set email alerts
|

A Systems-level Characterization of the Differentiation of Human Embryonic Stem Cells into Mesenchymal Stem Cells*[S]

Abstract: Mesenchymal stem/stromal cells (MSCs) are self-renewing multipotent cells with regenerative, secretory and immunomodulatory capabilities that are beneficial for the treatment of various diseases. To avoid the issues that come with using tissue-derived MSCs in therapy, MSCs may be generated by the differentiation of human embryonic stems cells (hESCs) in culture. However, the changes that occur during the differentiation process have not been comprehensively characterized. Here, we combined transcriptome, prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Cyclin D1 (encoded by CCND1 ) enhances the aggressive nature of CSCs by promoting cellular epithelial to mesenchymal transition (EMT), migration, proliferation, and drug resistance 24 . In addition, previous findings have highlighted RAF1 as a top promoter of mesenchymal stem cell (MSC) function 25 . MSCs have self‐renewing, secretory, and immunomodulatory (immune dampening) capabilities 25 and are known to regulate CSCs through paracrine mechanisms 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclin D1 (encoded by CCND1 ) enhances the aggressive nature of CSCs by promoting cellular epithelial to mesenchymal transition (EMT), migration, proliferation, and drug resistance 24 . In addition, previous findings have highlighted RAF1 as a top promoter of mesenchymal stem cell (MSC) function 25 . MSCs have self‐renewing, secretory, and immunomodulatory (immune dampening) capabilities 25 and are known to regulate CSCs through paracrine mechanisms 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous findings have highlighted RAF1 as a top promoter of mesenchymal stem cell (MSC) function 25 . MSCs have self‐renewing, secretory, and immunomodulatory (immune dampening) capabilities 25 and are known to regulate CSCs through paracrine mechanisms 26 . Stat5b (encoded by STAT5B ) has been characterized to induce EMT and stem‐like properties via Jak2‐Stat5a/b signalingy 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the mouse ESC dataset ( Yang et al , 2019 ) (PRIDE: PXD010621), the human glioblastoma dataset ( Recasens et al , 2021 ) (PRIDE: PXD020441) and the mouse adipocyte dataset ( Su et al , 2019 ) (PRIDE: PXD011525) are used for evaluating the stability of selected SPSs. The human ESC dataset ( Billing et al , 2019 ) (PRIDE: PXD004652), the HCT116 dataset ( Hahn et al , 2021 ) (PRIDE: PXD023703), the T-cell dataset ( Martinez-Fabregas et al , 2020 ) (PRIDE: PXD020964) and the AGS cell dataset ( Yin et al , 2020 ) (PRIDE: PXD005093) are included for independent validation of the reproducibility of the proposed framework. All other human phosphoproteomic datasets were curated from the qPhos database ( Yu et al , 2019 , http://qphos.cancerbio.info ) and its updated version ( http://qptm.omicsbio.info ).…”
Section: Methodsmentioning
confidence: 99%
“…This finding indicated that NEAT1 could promote the differentiation of NB4 cells (Zeng et al, 2014). In addition, NEAT1 increased during the differentiation of many kinds of cells, including embryonic stem cells, muscle cells, nerve cells, and glial cells (Lehnert et al, 2007;Mercer et al, 2010;Billing et al, 2019;Cui et al, 2019;Wang et al, 2019). NEAT1 has been shown to be highly expressed in hematopoietic stem cells, progenitors, and immune cells.…”
Section: Introductionmentioning
confidence: 90%